Public's perception toward the uses of renewable energy in residential area to create sustainable housing / Muhamad Aiman Fahmi Kamaruzaman and Mohd Dzulkarnaen Sudirman - Kamaruzaman, Muhamad Aiman Fahmi; Sudirman, Mohd Dzulkarnaen (2019)
This paper describes a new concept of painting work by using Smart Unmanned Aerial Vehicle (SUAV) that can do the painting work in the construction industry. This project idea comes from a concept idea that emerges from a combination of two different technology which is Unmanned Aerial Vehicle (UAV) and Spray Painting. The spray painting using a UAV, expected will be suitable for construction industrial applications because UAV can be variety of size especially at confine, narrow space and the height of building that give limitation of space for the labour to do the painting work. The SUAV is motivated by the potential of safety, accurate and fast painting work. The SUAV is a drone that has been custom fitted with an arm plus a spray. Painting using a UAV has the potential to produce actual (predictable and repeatable) painted appearance, to be low-cost, and importantly to avoid the need for scaffolding and ladders which is the safety of the worker in high-rise building due to fall is secure. The primary purpose of this study is to gain the current issue on painting work that used a conventional method that can cause of accident and hazard to the worker safety and innovate it to better painting work by using a painting UAV that is relevant to the concept of industry revolution 4.0.